GERAKAN MAHASISWA LAWAN DIABETES: EDUKASI SEKOLAH LOKAL TENTANG MANAJEMEN ASUPAN GULA DENGAN DUKUNGAN TEKNOLOGI KESEHATAN - Wijayanti, Putri Ameilya Wijayanti; Aris; Yulianto (Khazanah: Jurnal Mahasiswa, 2024)
Diabetes mellitus (DM), a disease with a rising global prevalence, has created a significant economic and social problem, which has placed a financial burden on Indonesia’s National Health Insurance. Despite the widespread prevalence, public awareness regarding complications from DM remains low which has caused an inadequate adoption of healthy lifestyle practices, such as regular blood sugar monitoring. The aim of this study is to develop effective health promotion strategies by involving health students who will take responsibility schools in the surrounding area, through programs integrated with regular health technology introductions. This pre-experimental study uses a one-group pre-test-post-test design to assess changes in students' knowledge and attitudes toward DM and daily blood sugar management using technology, based on a survey administered before and after the intervention. The results showed that the role of health students in educating others about DM and daily blood sugar management, supported by the use of technology such as mobile applications or AI-based tools can increase the knowledge of students at each level: elementary school, junior high school, and senior high school. Enhancing knowledge regarding diabetes mellitus, particularly in blood sugar level management, can help prevent the onset of DM and mitigate its complications, which can contribute to decreasing its prevalence. This supports the government in building Sustainable Development Goal 3 on healthy and prosperous living.